Creation of a participatory database of bioenergy projects - Benoit Delcroix; Diana Clarisse MontaÃ±o Navarro; Simon BarnabÃ©; Patrice Mangin (Center for Science and Technology, IAIN Surakarta, 2019)
Bioenergy is part of the solution to decarbonize energy systems and the economy, and to decrease greenhouse gases emissions drastically. The main goal of this work is to present a participatory database of bioenergy projects, initially based on information available on the International Energy Agency website. This new database aims at being updated over time through data crowdsourcing and being easily exportable in a spreadsheet for further processing. It provides numerous information about bioenergy projects around the world like the types of technology, inputs, outputs, financial information and project status. A detailed overview of the current database is presented, as well as the modus operandi suggested to improve over time this resource through voluntary contributions. The growing quality of this database will serve future research projects and analysis, while being a relevant tool to contribute to the success of the bioenergy sector.